2013
DOI: 10.1186/1479-5876-11-19
|View full text |Cite
|
Sign up to set email alerts
|

TNF gene polymorphisms in cystic fibrosis patients: contribution to the disease progression

Abstract: BackgroundIt is well known that the disease progression in cystic fibrosis (CF) patients may be diverse in subjects with identical mutation in CFTR gene. It is quite possible that such heterogeneity is associated with TNF-α and/or LT-α gene polymorphisms since their products play a key role in inflammation. The aim of the study was to investigate the possible roles of TNF gene polymorphisms in CF disease phenotype and progression.Methods198 CF patients and 130 control subjects were genotyped for both TNF-α–308… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Clinical data have reported that CF complications with TNF gene polymorphisms coupled with high serum TNF production are associated with decreased bone density [58]. Consistently, our experiments with TNF-stimulated CF osteoblasts showed both enhanced production of RANKL and defective production of OPG and thus support a link between the high levels of TNF and osteoclastogenesis.…”
Section: The Cftr Corrector C18 Reduces Rankl Production In Cf Osteobsupporting
confidence: 89%
“…Clinical data have reported that CF complications with TNF gene polymorphisms coupled with high serum TNF production are associated with decreased bone density [58]. Consistently, our experiments with TNF-stimulated CF osteoblasts showed both enhanced production of RANKL and defective production of OPG and thus support a link between the high levels of TNF and osteoclastogenesis.…”
Section: The Cftr Corrector C18 Reduces Rankl Production In Cf Osteobsupporting
confidence: 89%
“…ECTR DNA is only one of many species of extrachromosomal mammalian DNA, some of which are found in healthy cells from normal tissues. These extrachromosomal DNA species can be restricted to specific cell types such as the T- and B-excision circles generated during V(D)J recombination in lymphocytes ( 42 ), while others, including non-repetitive microDNAs and repetitive elements derived from satellite DNA and 5S ribosomal DNA, can be found in healthy cells from multiple organs ( 3 , 4 ). On the other hand, certain extrachromosomal DNA species are associated with disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the heterogeneity among these studies was relatively high ( I 2 = 53%), we next conducted sensitivity analysis by successively excluding each observation. As shown in Figure B, after excluding those secondary osteoporosis patients (CF), we found that the GG genotype significantly increased the risk of osteoporosis (OR = 0.63, 95% CI: 0.51‐0.77, P < 0.0001, I 2 = 31%), indicating that this polymorphism may be a promising genetic marker, especially for predicting the risk of essential osteoporosis.…”
Section: Resultsmentioning
confidence: 79%
“…1 In addition, osteoporosis and related fragility fractures are also common complications in patients with other diseases, such as cystic fibrosis (CF), Crohn's disease and rheumatoid arthritis (RA). [2][3][4] However, despite the fact that the pathogenetic mechanisms of this Suo-Chao Fu, Ping Wang and Ming-Xing are contributed equally to this work. disease were intensively investigated, factors that contribute to the development of osteoporosis are rather complicated and yet need to be further defined.…”
Section: Introductionmentioning
confidence: 99%